Length of stay and economic consequences with rivaroxaban vs enoxaparin/vitamin K antagonist in patients with DVT and PE: findings from the North American EINSTEIN clinical trial program. (October 2014) - Bookhart, Brahim K.; Haskell, Lloyd; Bamber, Luke; Wang, Maria; Schein, Jeff; Mody, Samir H.
Abstract Objective: Venous thromboembolism (VTE) (deep vein thrombosis [DVT] and pulmonary embolism [(PE]) represents a substantial economic burden to the healthcare system. Using data from the randomized EINSTEIN DVT and PE trials, this North American sub-group analysis investigated the potential of rivaroxaban to reduce the length of initial hospitalization in patients with acute symptomatic DVT or PE. Methods: A post-hoc analysis of hospitalization and length-of-stay (LOS) data was conducted in the North American sub-set of patients from the randomized, open-label EINSTEIN trial program. Patients received either rivaroxaban (15 mg twice daily for 3 weeks followed by 20 mg once daily; n = 405) or dose-adjusted subcutaneous enoxaparin overlapping with (guideline-recommended 'bridging' therapy) and followed by a vitamin K antagonist (VKA) (international normalized ratio = 2.0–3.0; n = 401). The open-label study design allowed for the comparison of LOS between treatment arms under conditions reflecting normal clinical practice. LOS was evaluated using investigator records of dates of admission and discharge. Analyses were carried out in the intention-to-treat population using parametric tests. Costs were applied to the LOS based on weighted mean cost per day for DVT and PE diagnoses obtained from the Healthcare Cost and Utilization Project dataset. Results: Of 382 patients hospitalized, 321 (84%), had acute symptomatic PE; few DVT patients required hospitalization. Similar rates of VTE patients were hospitalized in the rivaroxaban and enoxaparin/VKA treatment groups, 189/405 (47%) and 193/401 (48%), respectively. In hospitalized VTE patients, rivaroxaban treatment produced a 1.6-day mean reduction in LOS (median = 1 day) compared with enoxaparin/VKA (mean = 4.5 vs 6.1; median = 3 vs 4), translating to total costs that were $3419 lower in rivaroxaban-treated patients. Conclusion: In hospitalized North American patients with VTE, treatment with rivaroxaban produced a statistically significant reduction in LOS. When treating DVT and PE patients, clinicians should consider newer anti-coagulants with less complex treatment regimens.